Branding consumerism: Cross-media characters and story-worlds at the turn of the 20th century. (November 2015) - Freeman, Matthew
This article will serve to provide a historicised intervention on the configuration of what have come to be known as cross-media characters, fictional story-worlds, and indeed media branding at the turn of 20th-century America. The study will examine a number of innovative cross-media practices that emerged during the first decade of the 20th century, practices encouraged by the slippage of commercial logos, fictional characters, and brands across platforms, which altogether occurred through the broader rise of modern advertising and the industrialisation of consumer culture. I offer two examples of what can be termed respectively as cross-textual self-promotion and cross-media branding during this historical period, grounded in such cultural factors as turn-of-the-century immigration, new forms of mass media – such as, most notably, newspapers, comic strips and magazines – and consumerism and related textual activities.